Adaptive Deep Learning eXperience (ADLX) and Adaptive Curriculum: The Foundation of Modern Learning for Inclusive and Effective Education in the Digital Age - Hani Arie Rachmanie; Bunyamin; Ishaq Nuriadin (Postgraduate, University of Mataram, 2025)
This study aims to explore the implementation of ADLX and adaptive curriculum as a foundation for the development of modern learning at the secondary education level. Using a descriptive qualitative approach, this study involved interviews with teachers at a foundation with junior high school, senior high school, and vocational high school levels. The researcher also directly observed the learning process in the classroom and analysed learning documentation such as lesson plans, syllabi, and evaluation records. The findings indicate that the implementation of ADLX within the framework of an adaptive curriculum is capable of creating a more active, personalised, and participatory learning environment, leading to student engagement in thinking, exploratory, and reflective processes. Additionally, the adaptive curriculum allows teachers to tailor teaching strategies to students' needs, resulting in more optimal learning outcomes. These findings contribute to the development of future learning models that not only rely on technology but also place students at the centre of the educational process. With the right approach, ADLX and the adaptive curriculum have great potential to drive educational transformation toward greater equity, relevance, and meaning in the digital age.